Perancangan Sistem Informasi Penjualan Berbasis Web pada Toko Vanza Bakery - Putri, Tiara Maharani Azkia; Arisandi, Desi; Perdana, Novario Jaya (STMIK Banjarbaru, 2023)
This study describes the design of a Web-Based Sales Information System at Vanza Bakery using the Waterfall Software Development Life Cycle (SDLC) method development system. Currently Vanza Bakery in the sales process still uses conventional business, namely how to sell directly, face to face with buyers to make transactions. In addition, Vanza Bakery provides orders via whatsapp for prospective buyers who want to customize cakes. Vanza Bakery as a bread and cake business requires an efficient system to manage its sales. In this development, an initial needs analysis is carried out which then creates a detailed system design before entering the development, testing and implementation stages based on structured stages and allows good monitoring from start to finish. The result is a web-based system that allows customers to place orders online. The implementation of this system is expected to increase productivity and customer experience and optimize business management processes at Vanza Bakery.Keyword: Sales Information System; Cake ordering; SDLC Waterfall MethodÂ AbstrakPerancangan Sistem Informasi Penjualan Berbasis Web pada Toko Vanza Bakery ini menggunakan sistem pengembangan metode Software Development Life Cycle (SDLC) Waterfall. Saat ini Vanza Bakery dalam proses penjualannya masih menggunakan bisnis konvensional yaitu cara berjualan secara langsung, bertatap muka dengan pembeli untuk melakukan transaksi. Selain itu, Vanza Bakery menyediakan pemesanan via whatsapp untuk calon pembeli yang ingin custom kue. Toko Vanza Bakery sebagai bisnis roti dan kue memerlukan sistem yang efisien untuk mengelola penjualannya. Dalam pengembangan ini, dilakukan analisis kebutuhan awal yang kemudian dibuat desain sistem yang terperinci sebelum memasuki tahap pengembangan, pengujian dan implementasi berdasarkan tahap-tahap yang terstuktur serta memungkinkan pemantauan yang baik dari awal hingga akhir, Hasilnya adalah sistem berbasis web yang memungkinkan pelanggan untuk melakukan pemesanan secara online. Impleentasi system ini diharapkan akan meningkatkan produktivitas dan pengalaman pelanggan dan mengoptimalkan proses manajemen bisnis di Toko Vanza Bakery.Â